Distribution of HBcAg in hepatitis B detected by immunoperoxidase staining with three different preparations of anti-HBc antibodies. Issue 3 (March 1989) - Kakumu, S; Arao, M; Yoshioka, K; Tsutsumi, Y; Inoue, M
Abstract : To evaluate the role of the expression of hepatitis B core antigen (HBcAg) in liver cell damage the immunoperoxidase staining pattern of cryostat liver biopsy specimens from 16 chronic carriers of hepatitis B surface antigen (HBsAg) was investigated using three different kinds of anti-HBc antibodies. Polyclonal antibody prepared from recombinant HBcAg seemed to be more sensitive in detecting HBcAg than did monoclonal antibody from the same antigen. The topographical distribution of HBcAg detected by these two antibodies was similar, showing a close correlation to the histological activity of disease. Furthermore, the predominant localisation of cytoplasmic HBcAg usually reflected an active and severe ongoing hepatitis. On the other hand, monoclonal antibody prepared from purified Dane particles resulted in the prominent cytoplasmic staining for HBcAg regardless of histological severity of the hepatitis. The quantitative expression and topographical distribution of HBcAg depended on the type of anti-HBc antibodies used.